Implementation of Explicit Instruction Learning Model to Increase Practical Skills Achievement of Vocational School Students - bambang sudarsono; fatwa tentama; Surahma Asti Mulasari; Tri Wahyuni Sukesi; Sulistyawati Sulistyawati; Fanani Arief Ghozali; Herman Yuliansyah; Lu'lu' Nafiati; Prabandari Listyaningrum; Wegig Pratama (VANOS Journal of Mechanical Engineering Education, 2022)
Practical skills are competencies that are needed by SMK graduates to improve the work readiness of SMK students. Learning achievement of practical skills can be improved by selecting the right learning model. The purpose of this study was to determine the application of the Explicit Instruction learning model for students of the Light Vehicle Engineering Skills Competency Vocational School (TKR) and to find out how much increased practical learning achievement of TKR Vocational School students after the application of the Explicit Instruction model. The research model is classroom action research (Classroom Action Research). The subjects of this study were students of SMK Muhammadiyah Bambanglipuro TKR Expertise Competence, amounting to 25 students. The data collection technique used was a test with a practical performance sheet instrument. The practice performance sheet is validated by industry experts. After being applied, the results of the practical exam assessment were analyzed descriptively. The results showed that the Explicit Instruction learning model could be applied well by students of SMK Muhammadiyah Bambanglipuro TKR Expertise Competence. After the implementation of the Explicit Instruction learning model, there was an increase in the average score of the competency aspect of practical skill achievement in each research cycle. The aspect of work preparation in the first cycle is 1.44, the second cycle is 2.32 and the third cycle is 2.88. The competency aspect of work knowledge in the first cycle is 1.64, the second cycle is 2.24 and the third cycle 3. While the work skill competency aspect in the first cycle is 1.56, the second cycle is 1.8 and the third cycle is 3.16.